Analisis Tindak Tutur pada Wawancara Presiden Prabowo Bersama Enam Jurnalis pada Youtube Najwa Shihab (Kajian Pragmatik) - Yuwafa Faurelio Yahya; Adila Nisa Hamidah; Taswirul Afkhar (Jurnal Ilmu Bahasa dan Pendidikan Guru Sekolah Dasar, 2025)
This study analyzes President Prabowo's speech acts in an interview with six journalists and editors-in-chief on the program "Presiden Prabowo Answers" on Najwa Shihab's YouTube channel. Using a pragmatic approach and qualitative descriptive methods, this study identifies three types of speech acts: locution, illocution, and perlocution. The results show that Prabowo not only conveys information, but also inserts certain intentions and shapes public perception through a strategic speech style. This finding confirms that language in political communication plays an important role in building an image and influencing the audience.